REVIEWS (New blackfriars, 1970)
Book reviews are coming in this articles. THE OLD TESTAMENT AND CHRISTIAN FAITH, ed. Bernard W. Anderson THE CHRISTIANK MEANING OF THE OLD TESTAMENT, by Norbert Lohfink, S.J., trans. R. A. Wilson THE PARABLES OF JESUS IN MATTHEW 13, by J. D. Kingsbury. GALATIANS: A DISCUSSION OF ST PAUL'S EPISTLE (Householder Commentaries: No. 1), by John Bligh THEOLOGY AND MEANING, A Critique of Metatheological Scepticism, by Raeburne S. Heimbeck. DO RELIGIOUS CLAIMS MAKE SENSE?, by Stuart C. Brown. THE CHRISTIAN KNOWLEDGE OF GOD, by H. P. Owen. THE MORAL LIFE, by Oliver Johnson. RESPECT FOR PERSONS, by R. S. Downie and Elizabeth Telfer. THE CHRISTIAN NEW MORALITY, by O. Sydney Barr. MAKING MORAL DECISIONS, editor D. M. Mackinnon. MAN DIVIDED, by Stan Windass. DEATH AND IMMORTALITY, by Josef Pieper, trans. Richard and Ciara Winston. HOPE AND HISTORY, by Josef Pieper, trans. Richard and Ciara Winston. DEVELOPMENT OF CHRISTIAN DOCTRINE: SOME HISTORICAL PROLEGOMENA, by Jaroslav Pelikan.